EFFECT OF SUNFLOWER OIL AND SUNFLOWER SEED SUPPLEMENTATION ON THE PRODUCTIVITY AND FATTY ACID COMPOSITION OF COW MILK - Pavkovych С.; Vovk С.; Ohorodnyk Н.; Balkovskyi В.; Dudar І.; Tkachuk В.; Pashchak М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The article discusses the results of a study on how feeding lactating cows sunflower oil and sunflower seeds impacts milk production and the fatty acid composition of milk fat. The use of high-energy fat supplements has a positive effect on cow milk production, especially during early lactation when animals may struggle to consume enough feed to meet their genetically programmed productivity needs. Despite the presence of sufficient unsaturated fatty acids in the diet, cow milk contains small amounts of them due to biohydrogenation processes in the rumen, which are known to have a positive impact on human health. However, introducing plant oils into the diet harms rumen fiber digestion processes. Feeding oilseed seeds may be a way to reduce the negative impact of unsaturated fatty acids on rumen microbial activity, thereby increasing milk production and quality. The study was conducted during the winter housing period. After a preparatory period, cows were divided into three groups of five each. During the study period, cows in the first group received a ration without fat supplements. Cows in the second group had sunflower oil added to their ration, replacing a portion of concentrates, at a rate of 3 % of dry matter. Cows in the third group were fed sunflower seeds, replacing a portion of concentrates equivalent to 3 % oil of dry matter. Feeding lactating cows with sunflower oil increased milk yield and lactose content, while fat-corrected milk yield, fat, protein, lactose content, and milk fat and protein yields decreased. This fat supplement reduced the content of C12-C16 and saturated fatty acids in milk fat, while increasing the content of C18, mono- and polyunsaturated fatty acids. Feeding sunflower seeds to cows increased milk yield, milk fat, protein, lactose content and milk fat, protein and lactose yields. Introducing this fat supplement into the ration reduced the content of C12-C16 and saturated fatty acids in milk fat while increasing the content of C18, mono- and polyunsaturated fatty acids.